The Development Strategy of The Atozz Sandals Product Using The QFD Method - Shanty Dhea Permatasari; Rita Ambarwati (Jurnal Bisnis dan Manajemen, 2023)
Atozz brand sandals are sandal products that will continue to develop in the future, so there are still many things to improve from this product. Therefore, this research aims to determine what consumers expect from Atozz sandals products in the future regarding improving the deficiencies in the products. This development research uses the Quality Function Deployment (QFD) method. The results of this study concluded that the attributes can be prioritized first on the attribute of always doing service consistently. The second development is improving the selection of raw materials starting from making with strong glue. This development can make the products not easily separated when exposed to water, and the product is more durable and long-lasting. The development of proper packaging is also essential to maintain product durability. Moreover, the third development is designing various sizes according to the desires and needs of consumers in order to attract customer interest in purchasing the product.